2018
DOI: 10.3390/toxins10020049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zearalenone Exposure on the TGF-β1/Smad3 Signaling Pathway and the Expression of Proliferation or Apoptosis Related Genes of Post-Weaning Gilts

Abstract: Zearalenone (ZEA) is an estrogenic toxin produced by Fusarium species, which is widely distributed and posed a great health risk to both humans and farm animals. Reproductive disorders associated with ZEA such as premature puberty, infertility and abortion have plagued the animal husbandry, but the molecular mechanism is unclear. Because transforming growth factor-β1 (TGF-β1) signaling pathway is involved in the proliferation and apoptosis of cells, proliferating cell nuclear antigen (PCNA), B-cell lymphoma/le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…We observed an increase in the mRNA and protein expression levels of GHR following ZEA and EB treatments compared with the control. This observation raises the question of whether one signalling pathways upregulates the expression of GHR by EB, probably similar to that mediated by ZEA (Zhou, Yang, Shao, et al, 2018a) or other mechanisms. However, the higher decline in GHR expression levels following EB treatment than that with ZEA treatment is contradictory to the uterine index, which creates a new topic of interest for the further research.…”
Section: The Effects Of Zea On Uterine Weight and Morphological Strmentioning
confidence: 99%
“…We observed an increase in the mRNA and protein expression levels of GHR following ZEA and EB treatments compared with the control. This observation raises the question of whether one signalling pathways upregulates the expression of GHR by EB, probably similar to that mediated by ZEA (Zhou, Yang, Shao, et al, 2018a) or other mechanisms. However, the higher decline in GHR expression levels following EB treatment than that with ZEA treatment is contradictory to the uterine index, which creates a new topic of interest for the further research.…”
Section: The Effects Of Zea On Uterine Weight and Morphological Strmentioning
confidence: 99%
“…OTA is carcinogenic in rodents and nephrotoxic in many mammal species; it has been also classified by IARC as possibly carcinogenic to humans and its presence in breast milk has been widely outlined [ 5 ]. The biomonitoring of ZEA is also important due to its toxic effects mainly on the reproductive system [ 6 ]; moreover, ZEA contamination was previously described in breast milk in Italy [ 7 ]. Consumers can be at risk of mycotoxins exposure both directly, by consuming contaminated grains, seeds, and dried fruits, or indirectly, by consuming contaminated animal source food (e.g., milk) derived from animals exposed to these contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5(a) , 60 μ g/ml EAEG treatment for 24 h reduced the cell viability to 64.68%, and this effect was partially offset by the cotreatment with 5 mM 3MA ( Figure 5(a) ), which inhibited significantly the autophagy induced by EAEG ( Figure 5(b) ). Furthermore, EAEG significantly decreased the level of PCNA and MCM7, two widely used cell proliferation markers [ 19 ], and this effect was also partially abrogated by 3MA ( Figure 5(b) ). We thus concluded that EAEG elicited a cytostatic effect on cancer cells through blocking autophagy-mediated cell proliferation rather than inducing apoptosis.…”
Section: Resultsmentioning
confidence: 98%